2002
DOI: 10.1577/1548-8675(2002)022<1393:rvocir>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment Variation of Crappies in Response to Hydrology of Tennessee Reservoirs

Abstract: Black crappies Pomoxis nigromaculatus and white crappies P. annularis were sampled to index recruitment in seven Tennessee reservoirs (four main‐stem and three tributary storage impoundments). Crappie recruitment in tributary storage impoundments appeared to be consistently higher in years of high discharge during the prespawn period (1 January–31 March). A similar relation was found in one main‐stem impoundment; however, crappie recruitment in two main‐stem impoundments was inversely related to discharge duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 15 publications
0
41
0
Order By: Relevance
“…The water level (m) and flow data (m 3 /s) were separated into four periods: (1) January through March was considered winter: (2) April through June was considered spring; (3) July through September was considered summer; and (4) October through December was considered fall. Previous researchers (Maceina & Stimpert, 1998;Sammons et al, 2002) have found hydrological conditions before spawning was related to crappie year-class strength, so the fall period before the spawn were also evaluated in the regression analyses for each sportfish species and was referred to as pre-spawn fall.…”
Section: Methodsmentioning
confidence: 99%
“…The water level (m) and flow data (m 3 /s) were separated into four periods: (1) January through March was considered winter: (2) April through June was considered spring; (3) July through September was considered summer; and (4) October through December was considered fall. Previous researchers (Maceina & Stimpert, 1998;Sammons et al, 2002) have found hydrological conditions before spawning was related to crappie year-class strength, so the fall period before the spawn were also evaluated in the regression analyses for each sportfish species and was referred to as pre-spawn fall.…”
Section: Methodsmentioning
confidence: 99%
“…False predictions have been applied elsewhere to successfully answer questions of biological processes. For example, residual analysis of linear models is used as a fisheries management tool to assess year class variability for some species of game fish (Maceina 1997;Sammons et al 2002). In the case of the models presented in this paper, residuals were categorical misclassifications of observed versus predicted category.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, hydrological factors (both pre-and postspawning) have been linked to recruitment in southeastern reservoirs. Strong year-classes are associated with years with short retention time or high discharge before spawning (Maceina and Stimpert 1998;Sammons and Bettoli 2000;Sammons et al 2002;Maceina 2003) or years with long retention time after spawning (Maceina and Stimpert 1998;Maceina 2003). Speculation regarding the mechanism centers on the possibility that increased precipitation (and resultant short retention time) during winter may increase primary production and food for first-feeding crappies (Maceina 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Via modeling, Allen and Miranda (2001) demonstrated that environmental fluctuation modulates densitydependent recruitment responses. In empirical studies, recruitment to age 1 has been strongly correlated with reservoir hydrology (i.e., discharge, retention) either before (Maceina and Stimpert 1998;Sammons and Bettoli 2000;Sammons et al 2002;Maceina 2003) or during (Mitzner 1981;Beam 1983;McDonough and Buchanan 1991) spawning. High discharge and short retention before spawning are hypothesized to either cue enhanced crappie reproduction or spur primary production to enhance food resources for young crappies (Maceina and Stimpert 1998;Maceina 2003).…”
mentioning
confidence: 99%